2007
DOI: 10.1080/00288230709510299
|View full text |Cite
|
Sign up to set email alerts
|

Pasture responses to phosphorus and nitrogen fertilisers on East Coast hill country: Total production from easy slopes

Abstract: A series of small, mowed plots, excluded from grazing, were established on flat to easy sloping (up to 15°) pastures on farms from Wairoa (northern Hawke's Bay) to Moeraki (North Otago) with contrasting degrees of spring, summer and autumn dryness, to evaluate the pattern of pasture responses to a range of nitrogen (N) fertiliser rates, and associated soil phosphorus (P) levels. Mean annual rainfall ranged from 474 (Marlborough) to 1348 mm (Wairoa) with all farms having an associated range in spring/summer/aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 16 publications
0
41
1
Order By: Relevance
“…This was quite different from the "diminishing returns" effect of increasing N fertiliser rate on pasture response recorded on flatter sites in the associated trial series (Gillingham et al 2007), and in results published for ryegrass:clover pastures (Ball & Field 1982;O'Connor 1982). This suggested that the soil on steep slopes was more deficient in available nitrate than was the soil on easier slopes.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…This was quite different from the "diminishing returns" effect of increasing N fertiliser rate on pasture response recorded on flatter sites in the associated trial series (Gillingham et al 2007), and in results published for ryegrass:clover pastures (Ball & Field 1982;O'Connor 1982). This suggested that the soil on steep slopes was more deficient in available nitrate than was the soil on easier slopes.…”
Section: Discussionmentioning
confidence: 57%
“…comm. ), and, except for the Wairoa and Wairarapa locations tended to be slightly lower than those measured on adjacent flatter slopes at the same time (Gillingham et al 2007). The values measured in Pumice soil at Wairoa (0.64 mg kg -1 ) and the value Table 2 Statistical significance of N fertiliser and Olsen soil P effects on total pasture dry matter production (kg Dm ha -1 ) in the early spring season (Jul-oct) from 2000 to 2002 at each site.…”
Section: Soil Nutrient Statusmentioning
confidence: 99%
See 3 more Smart Citations